University of Nevada System Comprehensive Plan, 1975-1979 - Nevada Univ., Reno.; Nevada Univ., Reno. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This document presents the University of Nevada System comprehensive plan for 1974-1979. Emphasis is placed on goals and objectives of state-supported higher education in Nevada; organization of the system and its major divisions; higher education issues and problems in Nevada in the 1970s; comparative analysis with other systems; a descriptive analysis of the University of Nevada system from July 1, 1968 to December 1974; and nonpublic postsecondary education in Nevada. Statistical data and a bibliography are included. (MJM)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Administration; Community Colleges; Higher Education; Master Plans; Private Colleges; State Colleges; State Universities; Statewide Planning; Nevada; Legal/Legislative/Regulatory Materials